COMPARAÇÃO ENTRE RESULTADOS COMPUTACIONAIS E EXPERIMENTAIS DO COMPORTAMENTO TÉRMICO DE UM AMBIENTE - Grings, Edi Terezinha de Oliveira (Revista Liberato, 2013)
This work presents a comparison between computational and experimental results of the thermal behavior of an air-conditioned and non-air-conditioned environment. In order to do that, climatic data on radiation, wind speed and temperature were monitored in the period between the 11th and 20th of January 2002 and a climatic file was created. Simultaneously, the temperatures of a test-room, situated on the 3rd floor of a building in the town of Porto Alegre, were collected as well as the temperatures of the adjoining rooms. The results of the thermal load and the environmental temperature obtained in the simulations were compared with the experimental data. There was a good agreement between the computational and experimental results.